PERANAN DESAIN INTERIOR DAN TATA LETAK RUANG KANTOR DALAM MENINGKATKAN KINERJA KARYAWAN - Astri Lestari, Putu (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2019)
Improving employee performance can be influenced by many things, including selfcompetence, motivation, support received, work environment, rewards or incentives, relationships between individuals in the company, etc. The atmosphere of the work environment such as office also affects employee performance. The office becomes the place where employees carry out their work needs to be supported by a clean and comfortable atmosphere. A clean and comfortable atmosphere can be created by paying attention to the interior design of the work space such as setting room lighting, conditional air condition, choosing the color of the paint wall, or the layout of the workspace such as the location of tables and chairs, and other furniture. Structuring interior design and workspace governance has an important role in improving employee performance. What must be considered in structuring the workspace is (1) the smooth communication between employees, (2) each employee gets a privacy area, (3) the selection of wall hangings to increase employee morale. Employee comfort in work must be considered This aims to increase employee morale so that employee performance can increase